Análisis hermenéutico de la sentencia 679-18-JP/20 de la Corte Constitucional del Ecuador: protección del derecho al acceso a medicamentos para pacientes con cáncer infantil (leucemia linfoblástica aguda) - Gualacata Narvaez, Karol Jazmin (2025)
Access to medicines has acquired legal relevance due to the problem that lies in the gap between constitutional obligations and the practical reality in the provision of medicines. Although the Constitution and court rulings order the State to guarantee access, hospitals and health centers face difficulties such as lack of budget, problems in the supply chain and deficiencies in distribution. In addition, the lack of coordination between public policies, national production, and regulation, aggravates the shortage of essential medicines, thus generating an impact on the health of patients, since the lack of essential medicines affects their quality of life, especially in catastrophic diseases such as acute lymphoblastic leukemia. The main objective of this research was to carry out a hermeneutic analysis of their arguments and interpretations on the right to access to medicines for patients with childhood cancer (acute lymphoblastic leukemia), in order to identify its legal implications and the scope of protection in the context of this right. The methodology used was documentary and qualitative, and we also worked with structured interviews directed to health professionals and experts in constitutional law. Based on the results, significant barriers are evident, such as a lack of resources allocated to health, implementation and coordination at the institutional level, and weakness in implementing measures such as public policies that help the proper functioning of the health system. Sentence 679-18-JP/20 highlights significant progress in guaranteeing access to medicines, but they suffer from structural problems such as lack of financing, implementation of public policies and corruption, which affects the health system, so it is necessary to take urgent measures to ensure constitutional rights, such as access to medicines.